2019
DOI: 10.1007/s11101-019-09602-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural classification and biological activities of Stemona alkaloids

Abstract: Stemona alkaloids represent a unique class of natural products exclusively known from the three genera Stemona, Stichoneuron, and Croomia of the monocotyledonous family Stemonaceae. Structurally they are characterized by a central pyrroloazepine core usually linked with two butyrolactone rings. The great diversity, comprising 215 derivatives, is created by the formation of additional CC linkages and oxygen bridges together with ring cleavages and eliminations of the lactone rings. Based on biosynthetic conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(54 citation statements)
references
References 143 publications
(179 reference statements)
1
52
0
1
Order By: Relevance
“…In the case of S . tuberosa , the main compound tuberostemonine ( 1 ) seems to be sensitive against oxidation since numerous derivatives of this alkaloid are suspected to be artefacts (Greger ). Evaluation of the plant material used in previous reports indicates regular co‐occurrence of 3,4‐dehydro‐δ‐tocopherol ( 6 ) with tuberostemonine ( 1 ) and its derivatives, or with croomine‐type compounds (Brem et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of S . tuberosa , the main compound tuberostemonine ( 1 ) seems to be sensitive against oxidation since numerous derivatives of this alkaloid are suspected to be artefacts (Greger ). Evaluation of the plant material used in previous reports indicates regular co‐occurrence of 3,4‐dehydro‐δ‐tocopherol ( 6 ) with tuberostemonine ( 1 ) and its derivatives, or with croomine‐type compounds (Brem et al .…”
Section: Resultsmentioning
confidence: 99%
“…These are structurally characterised by a pyrrolo‐ or pyrido [1,2‐α]‐azepine core. Greger () classified them into protostemonine, croomine and stichoneurine groups according to their core skeleton (Fig. ).…”
Section: Introductionmentioning
confidence: 99%
“…This has generated the need to search for new effective MDR modulators that have been isolated from natural products and that do not produce adverse side effects. A previous study reported that Stemona curtisii root extract, which contains Stemona alkaloids (Greger, 2006), modulated P-gp activity in human cervical cancer cells and the KB-V1 cell line (high P-gp expression). However, this was not the case with Multidrug resistant related protein-1 (MRP-1) activity in the MRP1-HEK293 cell line (high MRP-1expression).…”
Section: Discussionmentioning
confidence: 99%
“…The Stemona alkaloids are a class of structurally diverse natural products that act as the principle active constituents in Stemona plants (Stemonaceae) 15 – 20 . Known as “Bai Bu” in traditional Chinese medicine, Stemona plants have been used in East Asia for thousands of years as insecticides and anti-cough agents 15 , 16 , 19 , 20 . To date, more than 215 Stemona alkaloids have been isolated 15 , classified by Pilli 19 , 20 into eight structural groups (see Supplementary Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1 ). The attractive bioactivities 15 , 16 and unique polycyclic structures of these alkaloids have led to intense phytochemical, synthetic, and biomedical investigations, and many innovative total syntheses have been achieved 16 , 18 24 .…”
Section: Introductionmentioning
confidence: 99%